Snoring, sleep disturbance, and behaviour in 4-5 year olds. - Ali, N; Pitson, D; Stradling, J (1993)
Parents of 996 children aged 4-5 years identified consecutively from the Oxford health visitor register were asked to complete a questionnaire about breathing disorders during sleep. A total of 782 (78.5%) was returned. Ninety five (12.1%) children were reported to snore on most nights. Habitual snoring was significantly associated with daytime sleepiness, restless sleep, and hyperactivity. The questionnaire responses were used to select two subgroups, one at high risk of a sleep and breathing disorder and a control group. These children (132 in total) were monitored at home with overnight video recording and oximetry, and had formal behavioural assessment using the Conners scale. Seven (7/66) children from the high risk group and none from the control group had obvious sleep disturbance consequent on snoring and upper airway obstruction. Thus our estimate of the prevalence of sleep and breathing disorders in this age group is 7/996 or 0.7%. The high risk group had significantly higher nocturnal movement, oxygen saturation dip rates, and overnight pulse rates than the controls. Maternal but not paternal smoking was associated with the high risk group. Parents and teachers thought those in the high risk group were more hyperactive and inattentive than the controls, but only their parents thought them more aggressive. Significant sleep and breathing disorders occur in about 0.7% of 4-5 year olds. Children whose parents report snoring and sleep disturbance have objective evidence of sleep disruption and show more behaviour problems than controls.